GREEN SYNTHESIS OF SUPERPARAMAGNETIC IRON OXIDE NANOPARTICLE FROM FICUS CARICA FRUIT EXTRACT, CHARACTERIZATION STUDIES AND ITS APPLICATION ON DYE DEGRADATION STUDIES - P, Tharunya; V, Subha; S, KIRUBANANDAN; S, Sandhaya; S, Renganathan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The synthesis of nanoparticles (NPs) has become a matter of great interest in recent times due to their various advantageous properties and applications in a variety of fields. Metal NPs are being increasingly used in many sectors, and there is growing interest in the biological and environmental safety of their production. Methods: In this study, iron oxide NPs (Fe3O4-NPs) were synthesized from fruits of Ficus carica using a rapid, single step and completely green biosynthetic method by reduction of ferrous sulfate solution with F. carica ethanolic extract. The prepared Fe3O4-NPs were investigated by X-ray diffraction, Fourier transform infrared spectroscopy, and ultraviolet-visible spectroscopy. Results: The report emphasizes the effect of superparamagnetic Fe3O4-NPs on the degradation rate of hazardous dyes acid blue. Conclusion: To conclude, Fe3O4-NPs were prepared from fruits of F. carica using a rapid, single step and completely green biosynthetic method by reduction of ferrous sulfate solution with F. carica ethanolic extract. Keywords: Ficus carica, Ethanolic extract, Reduction, Ferrous sulfate, Superparamagnetic iron oxide nano particles, Dye degradation. Â 